Ethical Decision Diagrams on Donation After Cardiocirculatory Death Heart Transplantation Considering Organ Preservation Techniques. Issue 11 (November 2020) - Saemann, Lars; Karck, Matthias; Korkmaz-Icöz, Sevil; Wenzel, Folker; Szabó, Gábor
Abstract : Background: To overcome organ shortage, some centers accept hearts from cardiocirculatory determined death (DCD) donors for heart transplantation (HTx). DCD-HTx is attached with special ethical conflicts on the donor, family, and recipient side. Ethically motivated decisions also have to be made considering organ preservation techniques. However, ethical decision diagrams, which can be applied to find a final answer on the complex field of ethical questions, have not been developed yet. Methods: In an interdisciplinary group of clinical ethicists, transplantation surgeons, transplantation researchers, and perfusionists, after review of relevant literature, we focused on crucial ethical aspects on DCD-HTx in general and separated ethical conflicts with regard to the individual perspective of the donor, family, and recipient. Results: The leading aspect of discussion in the donor perspective mainly deals with the standoff period and with the definition of death. The perspective of recipients focuses on the wish to say farewell after the patient is deceased. In the recipient perspective ethical questions regarding organ procurement techniques occur. Conclusions: Ethical decision-making on DCD-HTx is complex, but it can be processed in a structured way by applying the decision diagrams that we have developed.